Improving Emergency Department Throughput Using Audit-and-Feedback With Peer Comparison Among Emergency Department Physicians. Issue 2 (24th March 2022) - Scofi, Jean; Parwani, Vivek; Rothenberg, Craig; Patel, Amitkumar; Ravi, Shashank; Sevilla, Mark; D'Onofrio, Gail; Ulrich, Andrew; Venkatesh, Arjun K.
Abstract : Supplemental Digital Content is Available in the Text. ABSTRACT: Introduction: We sought to determine if audit-and-feedback with peer comparison among emergency physicians is associated with improved emergency department (ED) throughput and decreased variation in physician performance. Methods: We implemented an audit-and-feedback with peer comparison tool at a single urban academic ED from March 1, 2013, to July 1, 2018. In the first study period, physicians received no reports. In the second period, they received daily reports. In the third period, they received daily, quarterly, and annual reports. Outcomes included patients per hour, admission rate, time to admission, and time to discharge. Results: A total of 272, 032 patient visits and 36 ED physicians were included. The mean admission rate decreased 6.8%; the mean time to admission decreased 43.8 minutes; and the mean time to discharge decreased 40.6 minutes. Variation among physicians decreased for admission rate, time to admission, and time to discharge. Low-performing outliers showed disproportionately larger improvements in patients per hour, admission rate, time to admission, and time to discharge. Conclusions: Automated peer comparison reports for academic emergency physicians was associated with lower admission rates, shorter times to admission, and shorter times to discharge at the departmental level, as well as decreased practice variation at the individual level.